ANALISIS METODE SIMPLE ADDITIVE WEIGHTING (SAW) DAN WEIGHTED PRODUCT (WP) UNTUK DECISION SUPPORT SYSTEM - Effendy, Zainollah (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
Process in awarding college scholarships, to determine who is eligible to receive scholarships for students of the Faculty of Engineering, University of Madura in particular, the selection process is carried out in accordance with the rules that have been set. The criteria in this study is the index value of academic achievement (GPA), parental income, the semester, the number of dependent parent, and age. Scholarship selection committee should take a decision in accordance with the principle of a 3T, namely: Target, Right Number, and Timely, if it is done well and properly will ensure that the results can be accounted for. This decision support system was instrumental in helping the College of Engineering to take the right decision. This research aims to design and build a decision support system of determining candidate grantee using Fuzzy MADM ( Multi - Attribute Decision Making ) with the completion of the analysis of Simple Additive Weighting Method ( SAW ) and Weighted Product ( WP ) . These models have been able to select the best alternative from a number of alternatives , in this case meant that alternatives are eligible to receive scholarships based on criteria determined in accordance scholarship program guidelines . Research carried out by finding the weights for each attribute . Then a ranking process that will determine the optimal alternative of each candidate grantee . The problem is to solve a particular MADM case may be difficult to determine which method is most relevant between the SAW and WP method . Therefore, the analysis performed to determine the percentage level according to the most appropriate method between SAW or WP in the resolution of the problem Keyword : Standart Operating Procedure (SOP), Fuzzy MADM, SAW, WP